Advances and frontiers in multimodal discourse analysis - Feng, D.; Zhang, D.; O'Halloran, Kay (Zhongguo Shehui Kexueyuan * Yuyan Yanjiusuo, 2013)
From the 1990s, the multimodal turn in systemic functional linguistics and discourse analysis makes multimodal discourse analysis a popular topic in linguistics and communication studies. In recent years, multimodal studies become to focus on the inter-disciplinary systematic analysis of multimodal meaning making resources and empirical studies, rather than simply applying linguistic theories to non-linguistic modes like image and gesture. As a result, the new discipline of multimodality with its own theoretical framework and analytical method is emerging. On the one hand, inter-disciplinary frameworks integrating linguistics, media and communication studies, cognitive science and so on are been applied to the analysis of complex multimodal systems; on the other hand, new research tools and methods using digital technologies such as visual modeling and concordance are been developed. The theories and methods of multimodal discourse analysis are also applied to education research, media studies, courtroom discourse research and so on.